Tribological properties of black phosphorus nanosheets as oil-based lubricant additives for titanium alloy-steel contacts - Qingjuan Wang; Tingli Hou; Wei Wang; Guoliang Zhang; Yuan Gao; Kuaishe Wang (Royal Society Open Science)
The black phosphorus (BP) powders were prepared by high-energy ball milling with red phosphorus as the raw material, and then the BP nanosheets were obtained by liquid-phase exfoliation. The tribological properties of the BP nanosheets as oil-based lubricant additives were investigated by the ball-on-disc tribometer. Results show that compared with the base oil of liquid paraffin (LP), the coefficient of friction and wear rate of the BP nanosheets as the additives in liquid paraffin (BP-LP) are lower for the same loads. BP-LP lubricants could significantly improve the load-bearing capacity of the base oil for titanium alloy-steel contacts and show excellent friction-reducing and anti-wear properties. The surface morphologies and elemental compositions of the friction pairs were further analysed using an optional microscope, scanning electron microscope and X-ray photoelectron spectroscopy. The lubrication mechanism of BP-LP can be attributed to the synergistic effects between lamellar adsorption and interlayer shear of BP nanosheets.